EFFECT OF DIFFERENT CULTIVARS AND PREPARATION METHODS ON VITAMIN E, TOTAL FAT AND FATTY ACID CONTENT OF SOYBEAN - Vasantharuba, Liyanage, P.K.S.; Sivakanesan, R. (My University, 2006)
Soybean [Glycine max (L.) Merr.] has been considered an important crop in the world because of its unique nutritional composition. On an average dry matter basis, soybean contains about 20% fat. Soy fat contains a high proportion of essential fatty acids such as linoleic and linolenic and vitamin E. In this study vitamin E and linoleic and linolenic acid contents of four Sri Lankan soybean cultivars were estimated under different preparation methods. Soybean cultivars differs significantly (p<0.05) in fat content (17.9-21.1%) but not in vitamin E content (5.7-7.4 μg/g). These cultivars also differ significantly (p<0.05) in essential fatty acids like linoleic acid (91.2-107.6 mg/g of seed) and linolenic acid (13.9-17.9 mg/g of seed) contents. Soybean cultivars showed a significant correlation between vitamin E and linoleic acid and linolenic acid content. Among the 3 different preparation methods, the mean fat content of boiled (18.2%) and baked (18.3%) samples was significantly lower (p<0.05) than the control (PM 25 variety). Vitamin E content of pressure cooked (1.5 μg/g of seed), boiled samples (0.3 μg/g of seed) was significantly lower when compared to the control. Vitamin E was completely lost in baked sample. During pressure cooking, boiling and baking, the vitamin E loss was around 76, 95 and 100% respectively. The linoleic and linolenic acid contents of the control were significantly (p<0.05) higher than all processed samples. The linoleic acid content of the processed samples ranged from 83.9-99.5 mg/g of seed and linolenic acid from 10.9-17.6 mg/g of seed. The percentage loss of essential fatty acids in pressure cooking, baking and boiling was 9, 15 and 15% respectively. Different preparation methods showed a significant positive correlation between vitamin E and essential fatty acids